Penerapan Tax Planning dalam Upaya Meningkatkan Efisiensi Pembayaran Beban Pajak Penghasilan pada PT Bintang Kaltim Sangasanga Tahun 2018 - Muhammad Kadafi; Tiara Nur Anggraini (Politeknik Negeri Samarinda, 2022)
The purpose of this research is to know the influence of before and after the implementation of tax planning on the calculation of income tax of PT. Bintang Kaltim Sangasanga in order to suppress the minimum tax burden payment. The analysis tool used is Law No. 36-year 2008. The results of this research show that with the implementation of the Tax Planning method PT. Bintang Kaltim can be the payment of tax expenses during the period of 2018.